Tinjauan Yuridis Konsekuensi Akta Notaris Atas Penyalahgunaan Keadaan - Ach Rofiki Putra; Yusriel Billy Ibrahim; Fendy Setyawan; Firman Floranta Adonara (WELFARE STATE Jurnal Hukum, 2026)
An authentic deed drawn up by a notary, even though it has high legal force, can be revoked if it is made with elements of abuse of circumstances (misbruik van omstandigheden). One example is the case recorded in Decision Number 106 PK/Pdt/2020, where an agreement made before a notary was revoked due to an imbalance in bargaining position that was detrimental to one of the parties. This normative juridical research concludes that abuse of circumstances, especially economic advantage, is a form of defective will that makes the notarial deed not meet the requirements for a valid agreement as stipulated in Article 1320 of the Civil Code. This shows that the principle of freedom of contract is not absolute and must be based on the principles of justice and protection of the weaker party. In addition, notaries have legal and ethical responsibilities for the deeds they draw up. If proven negligent or biased, notaries can be subject to sanctions. This emphasizes the importance of notarial integrity in maintaining public trust.